Micellar Synthesis and Acid Hydrolysis of a Phosphoric Diamide - KHANWALKAR, ANURADHA; PRABHA, SHASHI (Asian Journal of Chemistry, 2010)
Phosphoric bis-(2,4-dimethoxyphenyl amide) chloride, a C—N—P containing bis-amide, has been kinetically examined (a rate maximum at 4.0 M) during hydrolysis in 0.01-7.0 M HCl at 40 ±0.5°C. Zwitter ionic-neutral (or protonated-neutral) and conjugate acid species have been assessed as the major reactive forms, undergoing bimolecular hydrolysis with P—N bond fission. Arrhenius parameters and other concepts support bimolecular mode with 3-4 water molecules involved in the transfer of proton, formation of transition state and overall hydrolysis. Out of 20, only 3 reaction routes operate during hydrolysis. Synthesis has been performed using both parent amine as well as POCl3 in the presence of meagre amount of CTAB.